Critical-angle x-ray transmission grating spectrometer with extended bandpass and resolving power > 10,000 - Heilmann, Ralf K; Bruccoleri, Alexander R; Kolodziejczak, Jeffery; Gaskin, Jessica A; O'Dell, Stephen L; Bhatia, Ritwik; Schattenburg, Mark L (arXiv.org, 2016)
Several high priority subjects in astrophysics can be addressed by a state-of-the-art soft x-ray grating spectrometer (XGS). An Explorer-scale, large-area (> 1,000 cm2), high resolving power (R > 3,000) XGS is highly feasible based on Critical-Angle Transmission (CAT) gratings, even for telescopes with angular resolution of 5-10 arcsec. Significantly higher performance can be provided by a CAT XGS on an X-ray-Surveyor-type mission. CAT gratings combine the advantages of blazed reflection gratings (high efficiency, use of higher diffraction orders) with those of transmission gratings (low mass, relaxed alignment and temperature requirements, transparent at high energies) with minimal mission resource demands. They are high-efficiency blazed transmission gratings that consist of freestanding, ultra-high aspect-ratio grating bars made from SOI wafers using anisotropic dry and wet etch techniques. Blazing is achieved through reflection off grating bar sidewalls. Silicon is well matched to the soft x-ray band, and existing silicon CAT gratings exceed 30% absolute diffraction efficiency, with clear paths for improvement. CAT gratings coated with heavier elements allow extension of the CAT grating principle to higher energies and larger angles, enabling higher resolving power at shorter wavelengths. We show x-ray data from CAT gratings coated with platinum using atomic layer deposition, and demonstrate blazing to higher energies and much larger blaze angles than possible with silicon. We measure resolving power of a CAT XGS consisting of a Wolter-I focusing mirror pair from GSFC and CAT gratings, performed at the MSFC SLF. Measurement of the Al Ka doublet in 18th order shows resolving power > 10,000, based on preliminary analysis. This demonstrates that currently fabricated CAT gratings are compatible with the most advanced XGS designs for future soft x-ray spectroscopy missions.